LYST Controls the Biogenesis of the Endosomal Compartment Required for Secretory Lysosome Function. (6th January 2015) - Sepulveda, Fernando E.; Burgess, Agathe; Heiligenstein, Xavier; Goudin, Nicolas; Ménager, Mickaël M.; Romao, Maryse; Côte, Marjorie; Mahlaoui, Nizar; Fischer, Alain; Raposo, Graça; Ménasché, Gaël; de Saint Basile, Geneviève
<x xml:space="preserve">Abstract</x> Chediak–Higashi syndrome (CHS) is caused by mutations in the gene encoding LYST protein, the function of which remains poorly understood. Prominent features of CHS include defective secretory lysosome exocytosis and the presence of enlarged, lysosome‐like organelles in several cell types. In order to get further insight into the role of LYST in the biogenesis and exocytosis of cytotoxic granules, we analyzed cytotoxic T lymphocytes (CTLs) from patients with CHS. Using confocal microscopy and correlative light electron microscopy, we showed that the enlarged organelle in CTLs is a hybrid compartment that contains proteins components from recycling‐late endosomes and lysosomes. Enlargement of cytotoxic granules results from the progressive clustering and then fusion of normal‐sized endolysosomal organelles. At the immunological synapse (IS) in CHS CTLs, cytotoxic granules have limited motility and appear docked while nevertheless unable to degranulate. By increasing the expression of effectors of lytic granule exocytosis, such as Munc13‐4, Rab27a and Slp3, in CHS CTLs, we were able to restore the dynamics and the secretory ability of cytotoxic granules at the IS. Our results indicate that LYST is involved in the trafficking of the effectors involved in exocytosis required for the terminal maturation of perforin‐containing vesicles into secretory cytotoxic granules. <inline-graphic xlink:href="ark:/27927/pgh3hv3fqpw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />